Single-cell detection of primary transcripts, their genomic loci and nuclear factors by 3D immuno-RNA/DNA FISH in T cells - Salataj, Eralda; Spilianakis, Charalampos G.; Chaumeil, Julie (Frontiers in Immunology, 2023)
Over the past decades it has become increasingly clear that higher order chromatin organization is involved in the regulation of genome activity and serves as an additional epigenetic mechanism that modulates cellular functions and gene expression programs in diverse biological processes. Dynamic allelic interactions and gene repositioning within the nuclear space can be of functional importance during the process of lymphoid differentiation and the regulation of immune responses. So far, proximity between chromatin regions can be revealed either by the sequencing of proximal genomic domains using ligation based-chromatin conformation capture methods (“3C”-based), or DamID approaches, on cell populations, or by the simultaneous visualization of several genomic loci within the 3D nuclear space in individual cells using Fluorescence In Situ Hybridization (FISH). Here, we present a detailed protocol to simultaneously detect nascent mRNA transcripts (3D RNA FISH), their genomic loci (3D DNA FISH) and/or their chromosome territories (CT paint) combined with various nuclear factors (immunofluorescence-IF). We delineate the application and effectiveness of this robust and reproducible protocol in several murine T cell subtypes (from embryonic stem cells to differentiating and activated T cells).